Student perceptions and proposals for promoting wellbeing through social relationships at university. Issue 9 (21st October 2022) - Priestley, Michael; Hall, Angela; Wilbraham, Susan J.; Mistry, Virendra; Hughes, Gareth; Spanner, Leigh
ABSTRACT: Whilst existing evidence has demonstrated the imperative of social integration, inclusion, and belonging for student mental health, students often report relational challenges, barriers, and stressors at university. Drawing on thematic analysis of six student co-creation panels conducted during the Student Minds University Mental Health Charter consultations, this paper aims to elucidate student perspectives and proposals for promoting mental health at university by enhancing interpersonal interactions and social relationships. In particular, student panels identified existing challenges and opportunities to address social isolation, conflict, and exclusion in interactions with peers, academic staff, and the local community. The findings of this paper both echo and develop the principles of good practice propounded by the University Mental Health Charter, whilst the implications for university policy in the context of the Covid-19 pandemic are also discussed.